Dopamine and epigallocatechin-3-gallate cross-linked coating demonstrates improved osteointegration of polyetheretherketone in rabbits. (February 2023) - Mao, Genwen; Sun, Qianqian; Jiang, Jiajun; Sun, Jianzhong; Wu, Tao; Cheng, Chi; Teng, Menghao; Zhao, Yuqi; Zhou, Xiaoling; Zhang, Hao; Bian, Weiguo
Graphical abstract: Highlights: It was first time to attempt to cross link polydopamine and epigallocatechin-3-gallate together to enhance osteointegration for polyetheretherketone. It showed that the cross-linked coatings provided phenolic hydroxyl and amino groups and enhanced hydrophilicity of the polyetheretherketone. It may lay the foundation for the further deployment of the cross-linked polydopamine and epigallocatechin-3-gallate coating in clinical practice. Abstract: The increasing demand for enhanced osteointegration calls for next-generation polyetheretherketone (PEEK) that can offer fast bone integration. Whether polydopamine (PDA) and epigallocatechin-3-gallate (EGCG) cross-linked coatings could improve osteointegration of PEEK remains unclear. Here, we fabricated a series of PDA and EGCG cross-linked coatings (PE coatings: P2E0.1, P2E0.5, P2E1, and P2E2 coatings) to enhance osteointegration of PEEK. The material characteristics of coatings were studied using scanning electron microscopy, X-ray photoelectron spectroscopy, micro-BCA tests, and static water contact angle tests. We evaluated the cytotoxicity, cell adhesion, and osteogenic effects of the coatings in vitro . Furthermore, the P2E0.5 coating was selected to coat porous PEEK scaffold to observe osteointegration using micro-computed tomography and histology in a rabbit. The results show that the PE coatings provide phenolic hydroxyl and amino groups and enhanced hydrophilicity of PEEK, especially in the P2E0.5 coating. Several lines of cellular evidence suggest that P2E0.5 coatings exhibit a noncytotoxic and excellent osteogenic effect. Compared with PEEK, the P2E0.5-coated PEEK shows higher values of bone volume, trabecular number, and trabecular thickness. This study suggests that the PE coating is a promising candidate for surface modification of PEEK and may lay the foundation for further application of PE coatings in clinical practice.